(untitled) - Harrington, Diana R (Englewood Cliffs, N. J, 1987)
This book includes material on arbitrage pricing theory, empirical research, and functional uses; it explains the development of modern portfolio theory and the capital asset pricing model from efficient market assumptions; it also discusses how the risk free and market rates of return are estimated; and uses examples to show how practitioners have used these theories in estimating the coast of capital, funding portfolios, and selecting stocks.
Tài chính doanh nghiệp nâng cao
Keywords: Arbitrage,Capital assets pricing model,Portfolio management